CONCEPTUALIZING THE GOAL AND SYSTEM MODELS OF ORGANIZATIONAL EFFECTIVENESS ?IMPLICATIONS FOR COMPARATIVE EVALUATION RESEARCH - Strasser, Stephen; Eveland, J. D.; Cummins, Gaylord; Deniston, O. Lynn; Romani, John H. (Journal of Management Studies, 1981)
The lack of comparative evaluation research on organizational-effectiveness models is the primary focus of this discussion. Problems in conceptually and operationally defining evaluation models, such as those in the goal and system model classes, are the proposed reason for this lack of comparative research. In this paper, goal and system models are formally defined in terms of their historical origins, underlying criteria and differing methods of application. A goal and system model classification continuum is also presented. Five comparative evaluation research questions are proposed and their implications for research are discussed. From a theoretical perspective this paper attempts to go beyond the sound foundation laid by Campbell (1977) in his discussion of these two schools of thought on organizational effectiveness.